Evaluation Of Job Analysis Methods By Experienced Job Analysts - Levine, Edward L.; Ash, Ronald A.; Hall, Hardy; Sistrunk, Frank (Academy of Management Journal, 1983)
The article discusses a research on job analysis methods being used by experienced job analysts. Job analysis is a process wherein jobs are subdivided into elements through the application of a formalized, systematic procedure for data collection, analysis and synthesis. Several job analysis methods were used in the study and evaluated by job analysts by means of a mailed questionnaire. Results indicated that opinions about job analysis are not attributable directly to specific features of a job analysis method.